MODEL PEMBELAJARAN KOOPERATIF UNYUK MENINGKATKAN AKTIVITAS BELAJAR SISWA - Dita Yuzianah (Delta: Jurnal Ilmiah Pendidikan Matematika, 2018)
This research aims to increase the activity of mathematic by minimize the manner of mathematic difficulty on  the  sub-material of integers and multiplication. This research has done at SMPN 2 Pejagoan Kebumen and at SMPN 8 Purworejo. In the class 7A of SMPN 2 Pejagoan Kebumen there are forty students are given “the pair checking” learning model and in the class 7A of SMPN 8 Purworejo there are thirty students given “the pair searching” learning model. There is an improvement on the implementation of “the pair searching” learning model on the sub-material of multiplication to the class 7A student of SMPN 8 Purworejo in the academic year of 2011/2012, it is marked by the first result of observation of study activity in the ask’s braveness and the give a piece of mind to the first cycle is twelve students and after the implementation of “the pair searching” learning model is twenty-two students. The result of motivation and farvor to follow of learning (to finish for the self assignment and active for doing assignment be given by teacher to the first cycle get eighteen students and the second cycle get twenty-five students. The student interaction in follow the learning activity of group for the first cycle get twelve students and the second cycle twenty-five students. The student’s relationship with the teacher during the process learning (in the team work) to the first cycle get twenty-two students and the second cycle get twnty-five students and the student participation during the learning process get twenty-five students and the second cycle get twenty-eight students. This is supported by result of satisfaction’s average 77,66 at the score distance very well, where as the first cycle get average 60,17 at the less score distance. From the result of the class measure research could be conclude that pair cheks learning model could be increase the student activity for the student seven A grade class SMPN 2 Pejagoan at the integer subject from the result get twenty-three students at the early learning become twenty-nine students at the first cycle and thirty-five students at the second cycle. The increase of the result study from 51,13 at the early learning become 61,33 the first cycle and the second cycle could be increase become 75,48 with the completeness 82,50.